2020
DOI: 10.1111/jgs.16507
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Palliative Care Needs of COVID‐19 Patients Receiving Comfort‐Directed Care

Abstract: Since then, the rapid increase in the number of patients with COVID-19 associated with acute respiratory distress syndrome (ARDS) 1 and high rates of mortality 2,3 has highlighted the critical need for high-quality end-of-life care. On March 31, 2020, an eight-bed Palliative Care Unit (PCU) was established at our institution for patients with COVID-19 whose surrogates opted to not initiate or continue life-sustaining therapies. To our knowledge, this is the first report describing COVID-19 patients receiving c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
3
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 5 publications
2
43
3
8
Order By: Relevance
“…Another case series of 30 hospitalized deceased patients showed that 76.7% of the patients used intravenous morphine but, again, effectiveness was not evaluated. [17] Results. Most experts recommended strongly (55.9%) or conditionally (27.9%) that patients presenting with serious COVID-19 and distressing breathlessness, despite optimal treatment of underlying causes, should be given low-dose opioids for the palliative treatment of breathlessness.…”
Section: Patients Presenting With Serious Covid-19 and Distressing Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case series of 30 hospitalized deceased patients showed that 76.7% of the patients used intravenous morphine but, again, effectiveness was not evaluated. [17] Results. Most experts recommended strongly (55.9%) or conditionally (27.9%) that patients presenting with serious COVID-19 and distressing breathlessness, despite optimal treatment of underlying causes, should be given low-dose opioids for the palliative treatment of breathlessness.…”
Section: Patients Presenting With Serious Covid-19 and Distressing Brmentioning
confidence: 99%
“…[29] Results: Most experts provided a strong (58.8%) or conditional ( Rationale: Psychological symptoms such as anxiety and agitation are highly prevalent in dying patients with COVID-19. [6,17] Psychosocial interventions in palliative care can relieve emotional and existential distress and improve quality of life. [34] Therefore, a rapid review recommended to healthcare professionals providing psychosocial care in palliative care for patients with COVID-19, [31] although data in COVID- 19 are not yet available.…”
Section: Patients With Serious Covid-19 In Palliative Care and Distrementioning
confidence: 99%
“…6 Only recently has evidence emerged to help characterise symptom burden and outcomes in end stage COVID-19, but with small patient numbers and focussed geographical locations. [7][8][9] Our primary aim was to further characterise the symptom profile, outcomes and symptom management requirements of hospitalised patients with COVID-19 referred to Hospital Palliative Care. Our secondary aim was to contextualise Palliative Care demands from COVID-19 against a 'typical' Palliative Care caseload pre-pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Em relação às temáticas, duas categorias sintetizam os principais aspectos abordados nos estudos: "Estratégias para implementação dos cuidados paliativos no enfrentamento da COVID-19" (17)(18)(19)21,23,25,(27)(28)(29)(30)(31)(32)35,36,(38)(39)(40)(41)(42)44) (19; 63,3%) e "Terapêutica paliativista no contexto da pandemia: desafios e contribuições" (16,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31,33,34,(36)(37)(38)(39)(40)(41)(43)(44)(45) (24; 80%).…”
Section: Resultsunclassified
“…Entre as estratégias utilizadas para implementação dos cuidados paliativos no enfrentamento da COVID-19, destacaram-se a telemedicina e a comunicação entre os atores envolvidos, (17)(18)(19)21,25,27,28,30,32,35,36,(38)(39)(40)(41)(42)44) o planejamento das ações, (17)(18)(19)21,23,25,32,35,(39)(40)(41)44) a utilização adequada dos equipamentos de proteção individual e outros materiais (19,21,27,28,36,39) e o uso de ferramentas de gestão como planos, diretrizes e protocolos. (18,21,23,25,27,28,30-32,35,39,40,42,44 ou cuidadores.…”
Section: Resultsunclassified